2014
DOI: 10.3944/aott.2014.14.0033
|View full text |Cite
|
Sign up to set email alerts
|

Missed isolated posterior malleolar fractures

Abstract: Isolated posterior malleolar fracture should be kept in mind in patients who present with pain at the posterior part of the ankle following a forced plantar flexion and/or axial compression injury. A 50° external rotation lateral radiograph can be useful in detecting the fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…[3][4][5][6] This case report highlights the upmost importance of a comprehensive history taking and detailed clinical examination. In this sense, the most common mechanism of injury is plantar flexion associated to axial load since in these conditions the impact is transferred to the posterolateral tibial lip, 4 to 8-fold superior than in any other position.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5][6] This case report highlights the upmost importance of a comprehensive history taking and detailed clinical examination. In this sense, the most common mechanism of injury is plantar flexion associated to axial load since in these conditions the impact is transferred to the posterolateral tibial lip, 4 to 8-fold superior than in any other position.…”
Section: Discussionmentioning
confidence: 99%
“…7 These injuries may occur isolated or in combination with other injuries, such as, trimalleolar fractures, proximal fibular fractures, syndesmotic injuries or low-energy tibial shaft spiral-type fractures. 3,4,8 In this line, Kukkonen and colleagues reported that a fourth of the tibial shaft spiral-type fractures were associated with posterior malleolus fractures. 8 Usually, these fractures are related to a specific injury mechanism comprising, plantar flexion in axial load at the moment of ground impact, supination or external rotation of the talus in axial load, or progressive external rotation of the talus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An isolated posterior malleolar fracture is also known as a Volkmann’s fracture or an Earle’s fracture [7] , [8] . This injury is easily missed on plain radiographs and requires awareness of the treating physician [9] . In the present study, we describe a patient with an isolated posterior malleolar fracture including the long-term follow-up, which has been reported in line with the SCARE statement [10] .…”
Section: Introductionmentioning
confidence: 99%